Nanocellulose derived from agricultural biowaste by-products–Sustainable synthesis, biocompatibility, biomedical applications, and future perspectives: A review - Md. Meraj Ansari; Yunji Heo; Kyoungtag Do; Mrinmoy Ghosh; Young-Ok Son (Carbohydrate Polymer Technologies and Applications)
Cellulose, a natural linear biopolymer composed of hierarchically arranged cellulose nanofibrils, presents a compelling avenue for sustainable nanocellulose synthesis from agricultural by-products. This innovative approach both mitigates organic waste and landfill disposal and unlocks the latent potential of nanocellulose, transforming agricultural residue into valuable resources. This paradigm shift towards sustainability resonates across diverse industrial sectors, particularly in biomedical research and development. In recent years, the remarkable attributes of nanocellulose, including its biocompatibility, low cytotoxicity, and exceptional water-holding capacity for cell immobilization, have propelled its adoption in various medical applications. From drug delivery systems to wound healing, tissue engineering, and antimicrobial treatments, nanocellulose has emerged as a versatile biomaterial. Moreover, the strategic integration of nanocellulose into composites and its structural functionalization enable customizing its properties for specific functions, further expanding its utility. This comprehensive review explores prominent types of nanocellulose—including cellulose nanocrystals, cellulose nanofibrils, and microbial or bacterial cellulose—elucidating their biomedical applications. This review underscores the sustainability principles underpinning its utilization by exploring the cellulose sources derived from biowaste and industrial processes for nanocellulose production. As a crucial component in a wide array of biomedical materials, nanocellulose both drives innovation and propels the advancement of biomedicine toward sustainability.